Analysis of the Influence of Revitalization, Technology Use, and Human Resources Competence on MSME Income - Frans Antoni Sihite; Yunita Pakpahan (Yayasan Ilomata, 2023)
The image of the Kesawan area is considered unsuitable as a place for culinary businesses, so it is very necessary to revitalize the area as one of the drivers for the development of the Medan city area. The revitalization carried out specifically in the MSME area in the food and beverage sector is targeted to be able to attract visitors from both inside and outside the city. The aim of the research is to analyze the influence of revitalization, use of technology and human resource (HR) competency on MSME income. The method used is a quantitative approach and data collection is carried out by distributing questionnaires. Data analysis was carried out using multiple regression analysis with the help of the SPSS program. The results of this research show that the variables of revitalization, use of technology and human resource competence have an influence on increasing MSME income after being hit by Covid-19.